2020
DOI: 10.1111/pim.12689
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine elevation correlates with T regulatory cells increase in acute Plasmodium vivax infection: A pilot study

Abstract: Background Disease‐tolerance mechanisms limit infection severity by preventing tissue damage; however, the underlying mechanisms in human malaria are still unclear. Tryptophan (TRP), an essential amino acid, is catabolized into tolerogenic metabolites, kynurenines (KYN), by indoleamine 2,3‐dioxygenase 1 (IDO1), which can induce Foxp3+ T regulatory cells (Tregs). In this study, we evaluated the relationship of these metabolites with Treg‐mediated tolerance induction in acute malaria infections. Methods We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…previous exposure (Gardinassi et al, 2018;Cordy et al, 2019). We recently observed that acute Plasmodium infection induced an IFN-γ-driven increment in serum kynurenines that correlated with an elevation in the frequency of circulating FoxP3 + T regulatory cells in a hypo-endemic Amazon region (Dos Santos et al, 2020). Our exploratory results grant a more detailed prospective analysis of the relationship between innate immunity, parasitemia, and the balance of pro and anti-inflammatory pathways in human malaria and its dynamics during multiple episodic infections.…”
Section: Discussionmentioning
confidence: 58%
“…previous exposure (Gardinassi et al, 2018;Cordy et al, 2019). We recently observed that acute Plasmodium infection induced an IFN-γ-driven increment in serum kynurenines that correlated with an elevation in the frequency of circulating FoxP3 + T regulatory cells in a hypo-endemic Amazon region (Dos Santos et al, 2020). Our exploratory results grant a more detailed prospective analysis of the relationship between innate immunity, parasitemia, and the balance of pro and anti-inflammatory pathways in human malaria and its dynamics during multiple episodic infections.…”
Section: Discussionmentioning
confidence: 58%
“…Malaria parasites are known to suppress host immune responses by inducing the expression of indoleamine 2,3 dioxygenase (IDO), which is the rate-limiting enzyme of the kynurenine pathway in mammals. [34][35][36] The metabolites along the kynurenine pathway have been implicated in the pathogenesis of murine and human cerebral malaria. 37 The shift in tryptophan metabolism towards the kynurenine pathway may lead to the reduction of 5-HT production.…”
Section: Discussionmentioning
confidence: 99%
“…IDO serves as a rate-limiting enzyme in tryptophan metabolism, leading to the production of kynurenine. Elevated levels of kynurenine resulting from IDO activity have been shown to inhibit T cell proliferation (Fallarino et al, 2003), and promote the differentiation of Tregs (Forteza et al, 2018). Furthermore, an overexpression of IDO has been linked to the enhanced polarization of THP1 cells into M2 macrophages (Dos Santos et al, 2020;Mezrich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of kynurenine resulting from IDO activity have been shown to inhibit T cell proliferation (Fallarino et al., 2003), and promote the differentiation of Tregs (Forteza et al., 2018). Furthermore, an overexpression of IDO has been linked to the enhanced polarization of THP1 cells into M2 macrophages (Dos Santos et al., 2020; Mezrich et al., 2010). In the context of hDPSCs, IDO plays a role in regulating an immunosuppressive phenotype that inhibits the proliferation of peripheral blood mononuclear cells (PBMCs) (Hossein‐khannazer et al., 2019; Tomic et al., 2011).…”
Section: Introductionmentioning
confidence: 99%